Modelling CF of tobacco industry based on PLC across the supply chain. (2016) - Qian, Xiaoyan; Li, Renwang; Cao, Yanlong; Ni, Yihua; Wu, Xinli
To mitigate global warming, companies are being compelled to control greenhouse gas (GHG) emission in the supply chain. As a fundamental quantisation parameter of carbon emission in product life cycle (PLC), carbon footprint (CF) captures the interest of governments, firms and consumers. However, calculating CF is a prerequisite to confirm or refute best practices and policies for controlling CF. This research examines the method of calculating CF of tobacco industry based on PLC. For different stages of PLC, it presents different models to measure CF at four stages respectively, through which firms especially tobacco industry could find out where carbon emits too much and then could implement corresponding measures to control or even reduce CF. Customers could consider the low-carbon product through carbon labels. For government or related organisations, it could open a new way to promote efficient emission reduction policies, which can control GHG and mitigate global warming.